PERAN MEDIA SOSIAL DAN BRAND AWARENESS DALAM KEPUTUSAN MEMILIH PERGURUAN TINGGI DI KOTA KENDARI - Inayah Abdillah Rabbani; An Najjar M. Thahir; Prisilia Moita, Pilsa (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
This study is motivated by the phenomenon of increasing social media users in Kendari City and the use of social media as a marketing channel by higher education institutions. The purpose of this study is to determine whether social media has an influence on student decision making in choosing a college in Kendari City with brand awareness as a mediating variable. The method used in this study is a survey, using a questionnaire distributed online. The sample in this study was 150 respondents. This study uses path analysis techniques and regression tests. The results of the study indicate that social media has a positive and significant effect on brand awareness; social media has a positive and significant effect on decision making; brand awareness has a positive and significant effect on decision making and brand awareness mediates the relationship between social media and decision making. This study provides evidence that optimizing marketing on social media has the potential to influence student decisions in building brand awareness of an institution, thereby influencing students' decisions to choose the college.